2016
DOI: 10.3748/wjg.v22.i34.7767
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-α -G308A polymorphism is associated with liver pathological changes in hepatitis C virus patients

Abstract: AIMTo investigate the association of tumor necrosis factor alpha (TNFα) -G308A polymorphism with different liver pathological changes in treatment-naïve Egyptian patients infected with hepatitis C virus (HCV) genotype 4.METHODSThis study included 180 subjects, composed of 120 treatment-naïve chronic HCV patients with different fibrosis grades (F0-F4) and 60 healthy controls. The TNFα -G308A region was amplified by PCR and the different genotypes were detected by restriction fragment length polymorphism analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 48 publications
0
7
0
1
Order By: Relevance
“…Cytokines play a key role in the immune response to mediate disease progression and viral infection [46].…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines play a key role in the immune response to mediate disease progression and viral infection [46].…”
Section: Discussionmentioning
confidence: 99%
“…Our results agree with other studies reported decreased miR-223 expression in HCC. Khairy et al reported significant decrease in expression level in HCC group compared to non HCC groups (Khairy et al, 2016). Shi et al mentioned that miR-223 down regulated in HCC samples compared to matched non-tumor liver tissue (Shi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…techniques, including ultrasonography, Computed Tomography (CT) and Magnetic Resonance (MRI), have potentially limiting factors, including their availability, costs, and reproducibility (Khairy et al, 2016). Thus, early detection of HCC is still challenging and requires novel, sensitive and specific biomarkers that could detect tumor at an early stage where curative therapy can be applied (Sakamoto et al, 2010).…”
Section: Imagingmentioning
confidence: 99%
See 2 more Smart Citations